Effects of emodin, a plant‐derived anthraquinone, on TGF‐β1‐induced cardiac fibroblast activation and function. Issue 11 (27th May 2021) - Carver, Wayne; Fix, Ethan; Fix, Charity; Fan, Daping; Chakrabarti, Mrinmay; Azhar, Mohamad
Abstract: Cardiac fibrosis accompanies a number of pathological conditions and results in altered myocardial structure, biomechanical properties and function. The signaling networks leading to fibrosis are complex, contributing to the general lack of progress in identifying effective therapeutic approaches to prevent or reverse this condition. Several studies have shown protective effects of emodin, a plant‐derived anthraquinone, in animal models of fibrosis. A number of questions remain regarding the mechanisms whereby emodin impacts fibrosis. Transforming growth factor beta 1 (TGF‐β1) is a potent stimulus of fibrosis and fibroblast activation. In the present study, experiments were performed to evaluate the effects of emodin on activation and function of cardiac fibroblasts following treatment with TGF‐β1. We demonstrate that emodin attenuates TGF‐β1‐induced fibroblast activation and collagen accumulation in vitro. Emodin also inhibits activation of several canonical (SMAD2/3) and noncanonical (Erk1/2) TGF‐β signaling pathways, while activating the p38 pathway. These results suggest that emodin may provide an effective therapeutic agent for fibrosis that functions via specific TGF‐β signaling pathways. Abstract : The effects emodin, a plant‐derived anthraquinone, on fibroblast activation and fibrosis induced by transforming growth factor beta 1 (TGF‐β1) were evaluated. Treatment with emodin inhibited fibroblast activation and collagen expression induced by TGF‐β1. Emodin also inhibited canonical TGF‐β1 signaling while stimulating activation of p38 mitogen activated protein kinases.